(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
In this research, the rice hull and coconut hull from agriculture waste were investigated. The lignin content within the rice and coconut hull were determined before and after pre-treatment. Response Surface Methodology (RSM) used to predict the optimal condition for the treatments and Fourier Transform Infrared (FTIR) to identify the lignin content. The interaction of NaOH concentration, contact time (CT), and sample weight was investigated to optimize the lignin removal percentage (%). The correlation coefficient, R2 for a quadratic model of rice hull lignin removal was 0.8863 while for coconut hull lignin removal in the linear model was 0.7998, as well as the 2FI model was 0.8892. The optimum condition for rice hull lignin removal predicted by RSM were10 M NaOH concentration, 1-hour CT and 0.5 g sample produced 32.45% lignin removal. While for coconut hull lignin removal were 10 M NaOH concentration, 12 hours CT, 0.5 g sample produced 59.47% removal of lignin. Results show that alkaline pre-treated rice hull and coconut hull able to be used to remove higher percentage of lignin.